A systems biology study of the angiogenic retina: identification of novel pathways and molecular markers relevant to angiogenesis-dependent diseases - Oliveira, Lilian Cristina Costa Alecrim de (2023)
Angiogenesis is the formation of new blood vessels from existing ones, a process that contributes to health, but which also participates in human diseases. Cancer and retinopathies are examples of these diseases and for which antiangiogenic drugs have already proven effective for their treatments. However, these drugs still have limited effectiveness and not all patients respond to therapy. Therefore, it is urgent to better understand the molecular mechanisms of angiogenesis for the development of a new generation of angiogenic inhibitors. One of the difficulties in studying angiogenesis is due to the fact that blood vessels grow within tissues, which is not always easily reproduced in the laboratory. Therefore, animal models are important to study angiogenesis. Among them, we highlight the OIR (oxygen-induced retinopathy), an animal model that reproduces several aspects of retinopathy of prematurity, an angiogenesis-dependent disease. In previous works, we demonstrated that the transcriptome of the OIR model can be used to predict the severity of another angiogenesis-dependent disease: breast cancer. In this thesis work, we expand these studies by determining the proteome and lipome of the OIR model, integrating them with the already existing transcriptome data, to build a system biology model of the angiogenic retina. This model allowed identifying a lipid signature of pathological angiogenesis that favors the formation of lipid droplets and the production of mead acid, a marker of essential fatty acid deficiency. Corroborating these data, the proteomic analysis also revealed an abundance of proteins related to the metabolism and pathways of lipoproteins, cholesterol, chylomicrons and triacylglycerol. In summary, the integration of results from different omics technologies into a system biology platform allowed a better understanding of the molecular bases of pathological angiogenesis, with the identification of pathways and molecular markers for the development of new therapeutic and diagnostic alternatives for dependent diseases of angiogenesis, such as cancer and retinopathies.